Temporal Variations of Atmospheric CO2 in Dehradun, India during 2009. Issue 6 (January 2013) - Sharma, Neerja; Nayak, Rabindra K; Dadhwal, Vinay K; Kant, Yogesh; Ali, Meer M
The present study reports the temporal variations of CO2 mixing ratio measured using Vaisala GMP-343 sensor (at 15 m height) in Dehradun (30.1 °N, 77.4 °E) during 2009. Being a valley station, the mixing ratios are controlled by biospheric processes but not by large scale transport phenomenon or local pollution. A distinct diurnal cycle varies from 317.9 ppm in the afternoon to 377.2 ppm in the morning (before sunrise). The minimum early morning (0700-1000 IST) drop and minimum afternoon (1300-1700 IST) trough observed during monsoon months are related to the enhanced vegetation activity due to rain at the site. The maximum night time (2200 IST to next day 0700 IST) build up of CO2 observed during monsoon season is associated with the increase in heterotrophic respiration due to high moisture content in the soil. This is also confirmed by the positive coherence between night time CO2 mixing ratio with soil respiration simulated from Carnagie-Ames-Standford Approach (CASA) model. The strong negative coherence with net ecosystem productivity (simulated from the same model) shows that observations captured the regional changes in emission and uptake of CO2 in atmosphere.